How to Maximize the Usefulness of Behaviour Change Conversations with Patients during Routine Dental Consultations. (2nd March 2022) - Goldthorpe, Joanna; Pretty, Iain; Hart, Jo; Cotterill, Sarah; Peters, Sarah
Abstract : Clinicians can use behaviour change techniques effectively in routine consultations in healthcare settings, including dentistry. Professional guidelines support their use for preventing and managing a range of dental diseases. Theory and evidence from behavioural science can inform effective behaviour change interventions. This article examines the relevance of these techniques to the whole dental team and how they can be implemented within routine dental consultations. CPD/Clinical Relevance: Guidance and recommendations on how to support patients to change behaviours to promote oral (and general) health.